IDENTIFIKASI TAHAPAN PENGEMBANGAN COMMUNITY BASED TOURISM DAN KERJASAMA ANTAR KOMUNITAS PADA DESA WISATA KEMBANG KUNING DAN TETEBATU NTB - Annisa Lazuardina; Shabrina Amalia Ghassani; Lalu Syafril Rahmadio; Zaki Alif Ramadhani (Warta Pariwisata, 2022)
Lombok is a Super Priority Destination for development by the Ministry of Tourism. The Tourism Village Program is also another priority in developing a destination so that people can have income without migrating to other areas. The Tourism Villages of Kembang Kuning and Tetebatu are pilot villages and both have entrances to Mount Rinjani and Swallow's Nest Waterfall. The system used by the two Tourism Villages is bottom-up so that people's awareness of tourism has grown and is well developed. Starting from the management of homestays, BumDes and also coordination between the communities has been good. In this study, the stages of the tourism village will be identified using Community Based Tourism theory to assess the impact and effectiveness of the tourism village. With the award for Tetebatu Tourism Village from UNWTO as the Best Tourism Village, this research is worth doing because the stages that have been carried out can be recorded and become best practice for villages that want to develop the concept of a tourism village using Community Based Tourism.